Enhancing the community engagement of Indonesian Palm Oil Companies through the implementation of the Social Life Cycle Assessment (SLCA) - Budiani, Indah (UI Scholars Hub, 2020)
As national economic stakeholders, businesses are now paying more attention to the broader issues involving the public, local, and social dimensions of development. The Indonesian palm oil companies, as key stakeholders in the economy, play a crucial role in directly supporting the improvement of the community's well-being. The paper analyses the implementation of the UNEP/SETAC Guideline of Social Life Cycle Assessment (SLCA) as a sub-category of “community engagement” implemented by Indonesian palm oil plantations. Using the qualitative approach, this study describes four distinctive models of community engagement to mitigate the negative and positive social impacts brought about by business activities. The study finds that there is no convincing effective approach to corporate community engagement for poverty reduction. The study also highlights the importance of including community stakeholders in the decision-making processes as the means to prevent conflict and to maintain company reputation. Other approaches, such as capacity building and social economic development, can also be effective as long as a thorough assessment is conducted in advance and the participation of the local community is ensured in developing the intervention plan.